Pengaruh Model Problem Based Learning Terhadap Hasil Pembelajaran Tematik Terpadu Siswa Kelas VI SD Negeri 055981 Beruam Kabupaten Langkat - Priska Nurlia Br Simanungkalit (LP3M KH Yazid Karimullah Institute, 2021)
The average student learning outcomes before using the problem based learning model (pre-test) in thematic learning in class VI was 67.75 and the standard deviation obtained was 11.12. The lowest score is 45 and the highest score is 85. The average student learning outcomes after using the problem based learning model (post-test) in thematic learning in class VI is 76.57 and the standard deviation obtained is 8.95. With the lowest value being 55 and the highest value being 90. Based on the calculation of the t-test, a tcount of 8.83 is obtained with db = 28 -1 = 27 with a significant level (